Pengembangan Kewirausahaan Produk Pangan Asal Pertanian dan Peternakan di Desa Cileles Kecamatan Jatinangor Kabupaten Sumedang - ELLIN HARLIA; Eulis Tanti Marlina; Yuli astuti (Media Kontak Tani Ternak, 2020)
Cileles Village has enormous potential, both from human resources and natural resources. The entrepreneurial atmosphere in Cileles Village has been formed with the emergence of home industry entrepreneurs such as banana chips, cassava chips, catering, resin sculpture, furniture business, farming / livestock business, bag convection business, and groceries business. Entrepreneurial activities carried out by the community in Cileles Village have various obstacles that can hinder the running of the business, including marketing, regeneration, knowledge of how to produce good processed food, use of labels, raw materials, and licensing. The marketing area carried out by entrepreneurs in Cileles Village is only around Jatinangor, so that their business is underdeveloped. Increasing knowledge of entrepreneurs in Cileles is needed, assistance to PKK members is one of them. The method used in this extension is through entrepreneurship training. The target is PKK members as many as 30 people. The training materials include simple bookkeeping with Google sheets, food safety training on good food processing, repairing packaging, repairing labels, choose an alternative product if raw material is difficult and assistance in preparing permits.